A review of the mite subfamily Harpirhynchinae (Acariformes: Harpirhynchidae)—parasites of New World birds (Aves: Neognathae) - Bochkov, Andre V; Oconnor, Barry M.; Klompen, Hans (Zootaxa, 2015)
Mites of the subfamily Harpirhynchinae (Acariformes: Cheyletoidea: Harpirhynchidae) associated with neognathous birds (Aves: Neognathae) in the New World are revised. In all, 68 species in 8 genera are recorded. Among them, 27 new species and 1 new genus are described as new for science: Harpyrhynchoides gallowayi Bochkov, OConnor and Klompen sp. nov. from Columba livia (Columbiformes: Columbidae) from Canada (Manitoba), H. zenaida Bochkov, OConnor and Klompen sp. nov. from Zenaida macroura (Columbiformes: Columbidae) from USA (Michigan), H. calidris Bochkov, OConnor and Klompen sp. nov. from Calidris minutilla (Charadriiformes: Scolopacidae) from USA (Kansas), H. actitis Bochkov, OConnor and Klompen sp. nov. from Actitis macularius (Charadriiformes: Scolopacidae) from Canada (British Columbia), H. charadrius Bochkov, OConnor and Klompen sp. nov. from Charadrius vociferus (Charadriiformes: Charadriidae) from USA (Texas), H. pluvialis Bochkov, OConnor and Klompen sp. nov. from Pluvialis dominica (Charadriiformes: Charadriidae) from USA (Ohio), H. bubulcus Bochkov, OConnor and Klompen sp. nov. from Bubulcus ibis (Pelecaniformes: Ardeidae) from USA (Florida), H. ixobrychus Bochkov, OConnor and Klompen sp. nov. from Ixobrychus exilis (Pelecaniformes: Ardeidae) from USA (Michigan), H. puffinus Mertins sp. nov. from Puffinus gravis (Procellariformes: Procellariidae) from USA (Florida), H. megascops Bochkov, OConnor and Klompen sp. nov. from Megascops asio (Strigiformes: Strigidae) from USA (Michigan), H. athene Bochkov, OConnor and Klompen sp. nov. from Athene canicularia (Strigiformes: Strigidae) from USA (Texas), H. coccyzus Bochkov, OConnor and Klompen sp. nov. from Coccyzus americanus (Cuculiformes: Cuculidae) from USA (Michigan), H. crotophaga Bochkov, OConnor and Klompen sp. nov. from Crotophaga ani (Cuculiformes: Cuculidae) from Suriname; Crassacarus Bochkov, OConnor and Klompen, gen. nov.: Crassacarus alexfaini Bochkov, OConnor and Klompen sp. nov. (type of genus) from Cardinalis cardinalis (type host) from USA (Michigan), Passerina ciris (unknown locality in North America) (Passeriformes: Cardinalidae), and Setophaga petechia (Passeriformes: Parulidae) from USA (Michigan), C. tinae Bochkov, OConnor and Klompen sp. nov. from Carduelis tristis (Passeriformes: Fringillidae) from USA (Wyoming), C. fritschi Bochkov, OConnor and Klompen sp. nov. from Bombycilla cedrorum (Passeriformes: Bombycillidae) from USA (Michigan), C. sialia Bochkov, OConnor and Klompen sp. nov. from Sialia currucoides (Passeriformes: Turdidae) from USA (Wyoming), C. melanerpes Bochkov, OConnor and Klompen sp. nov. from Melanerpes formicivorus (Piciformes: Picidae) from USA (Kansas); Neharpyrhynchus turdus Bochkov, OConnor and Klompen sp. nov. from Turdus migratorius (Passeriformes: Turdidae) from USA (Michigan), N. campylorhynchus Bochkov, OConnor and Klompen sp. nov. from Campylorhynchus brunneicapillus (Passeriformes: Troglodytidae) from USA (unknown locality), N. spizella Bochkov, OConnor and Klompen sp. nov. from Spizella passerina (Passeriformes: Emberizidae) from USA (various localities), N. quiscalus Bochkov, OConnor and Klompen sp. nov. from Quiscalus quiscula (Passeriformes: Icteridae) from USA (Michigan), N. agelaius Bochkov, OConnor and Klompen sp. nov. from Agelaius phoeniceus (Passeriformes: Icteridae) from USA (Michigan), N. bombycilla Bochkov, OConnor and Klompen sp. nov. Bombycilla cedrorum (Passeriformes: Bombycillidae) from USA (Michigan), N. vireo Bochkov, OConnor and Klompen sp. nov. from Vireo olivaceus (Passeriformes: Vireonidae) from USA (Florida), N. picidarum Bochkov, OConnor and Klompen sp. nov. from Colaptes auratus (type host), Melanerpes formicivorus, Melanerpes uropygidialis, and Picoides pubescens (Piciformes: Picidae) from USA (various localities); Perharpyrhynchus charadrius Bochkov, OConnor and Klompen sp. nov. from Charadrius vociferus (Charadriiformes: Charadriidae) from USA (Michigan). Harpyrhynchoides oenae lamorali (Fain, 1972) syn. nov. is synonymized with Harpyrhynchoides oenae (Fain, 1972). Harpirhynchoides agapornis (Fain, 1972) comb. nov. and Crassacarus cylindripalpus (Fritsch, 1954) comb. nov. are transferred from the subgenus Pseudoharpirhynchus Fain, Bochkov and Mironov, 1999 (type species Harpirhynchus agapornis Fain, 1972) of the genus Harpirhynchus Megnin 1877. The subgenus Pseudoharpirhynchus syn. nov. is synonymized with the genus Harpyrhynchoides. Diagnoses for the subfamily and all genera recorded in the New Word (Anharpyrhynchus Fain, 1972, Crassacarus gen. nov., Harpirhynchus, Harpyrhynchoides Fain, 1972, Fainharpirhynchus Bochkov and Galloway, 2013, Neharpyrhynchus Fain, 1972, Perharpyrhynchus Fain, 1972, Trichorhynchiella Fain, 1995) are provided. Keys to all harpirhynchine genera and all their species occurring in the New World are also given. A list of all harpirhynchine species and their hosts is compiled.